1996
DOI: 10.1021/ac950935b
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Jump Investigation of Alkyl Chain Length Effects on Sorption/Desorption Kinetics at Reversed-Phase Chromatographic Interfaces

Abstract: The influence of the alkyl chain length on the kinetics of solute retention at reversed-phase chromatographic surfaces is examined. A Joule-discharge temperature-jump relaxation experiment was used to monitor reversible sorption/desorption kinetics at C4- and C8-modified silica/solution interfaces. Biexponential sorption/desorption relaxation kinetics were observed for a charged fluorescent probe, 1-anilino-8-naphthalenesulfonate (ANS), on both C4- and C8-silica surfaces. Both relaxation rates on C4 surfaces w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For the cation to be adsorbed or captured by the surface, the ion has to penetrate the solvent layer adsorbed at the surface and to reorganize its own solvation sphere. Other studies have reported finite and relatively low adsorption rates for ionic molecules at surfaces. The adsorption rates of ionic probes are slower than a diffusion-controlled limit.…”
Section: 126 Sio2−polar Liquid Interfacementioning
confidence: 97%
“…For the cation to be adsorbed or captured by the surface, the ion has to penetrate the solvent layer adsorbed at the surface and to reorganize its own solvation sphere. Other studies have reported finite and relatively low adsorption rates for ionic molecules at surfaces. The adsorption rates of ionic probes are slower than a diffusion-controlled limit.…”
Section: 126 Sio2−polar Liquid Interfacementioning
confidence: 97%
“…Based on the stronger adsorption of pyrene, it was surprising that phenanthrene exhibited a slower adsorption rate; this could be due to the small dipole moment of phenanthrene, which increas-es its interaction with the aqueous solution phase compared to the other two (non-polar) PAH compounds and slows its rate of transfer across the hydrophobic interface. 47 To determine whether the PAH response conforms to a simple isotherm, the solution concentration dependence of the pyrene SERS signal was measured and fit to a Langmuir isotherm: 48 FIG. 8.…”
Section: Detection Of Polycyclic Aromatic Hydrocarbon Compounds On C1mentioning
confidence: 99%
“…The probes used in these previous studies were anionic and neutral molecules smaller than R6G + , 1-anilino-8-naphthalenesulfonate (ANS - ) and its neutral analogue N -phenyl-1-naphthylamine (1-NPN). The temperature jump experiments were of two kinds: a Joule-heating experiment, where silica was heated by passing an electrical current through the solution surrounding the silica, and a laser temperature jump experiment used with a silica colloidal dispersion . Because Joule heating required electrical current to be conducted through the sample, electrolyte concentrations were high so that the rate of heating was fast.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption and desorption kinetics at a C-4 interface appear to be unique, but the results also carry considerable uncertainty due to the biexponential form of the relaxation and the similarity of the two relaxation rates. The kinetics on a C-4 surface should differ from C-1 surfaces since solutes can partially partition into the alkyl chains, but the chain length is typically not long enough to fully solvate the molecule …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation